2005
DOI: 10.1038/nature04345
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the post-perovskite phase as an explanation for lowermost-mantle seismic properties

Abstract: Constraining the chemical, rheological and electromagnetic properties of the lowermost mantle (D'') is important to understand the formation and dynamics of the Earth's mantle and core. To explain the origin of the variety of characteristics of this layer observed with seismology, a number of theories have been proposed, including core-mantle interaction, the presence of remnants of subducted material and that D'' is the site of a mineral phase transformation. This final possibility has been rejuvenated by rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
138
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(165 citation statements)
references
References 28 publications
24
138
1
2
Order By: Relevance
“…The presence of a dominantly postperovskite D´´ layer is therefore consistent with regional variations in lower-mantle shear-wave anisotropy (see e.g. Hernlund et al, 2005;Wookey et al 2005).…”
Section: Introductionsupporting
confidence: 59%
“…The presence of a dominantly postperovskite D´´ layer is therefore consistent with regional variations in lower-mantle shear-wave anisotropy (see e.g. Hernlund et al, 2005;Wookey et al 2005).…”
Section: Introductionsupporting
confidence: 59%
“…In this region of the planet, anomalous features have been documented by seismology, including the ultralow velocity zones (ULVZ) which have been attributed to partial melt, chemical and thermal heterogeneities (3,4). Numerous studies of pure Mg (or Mg-rich) ppv have been undertaken to interpret these unusual seismic signatures (2,(5)(6)(7)(8)(9)(10)(11)(12)(13). Iron is likely to be an important component in ppv, and its incorporation in silicate ppv has been found to have a considerable influence on the properties of the phase.…”
mentioning
confidence: 99%
“…A lthough the postperovskite (pPv) phase transition in MgSiO 3 (1-3) is suggested to be strongly related to the deep-mantle DЉ seismic discontinuity (4)(5)(6), phase relations in more realistic chemical compositions, containing particularly aluminum and iron, are needed for further detailed investigations of this region. High-pressure experiments (7,8) demonstrated that magnesium silicate perovskite (Pv) is the major host of aluminum over the entire pressure (P) and temperature (T) range of the lower mantle, possessing Ϸ5 mol% of Al 2 O 3 in pyrolite and Ϸ20 mol% in MORB.…”
mentioning
confidence: 99%